Probing the Magnetic Interaction with Y-Doping in La0.7Ca0.3MnO3 Compounds by Critical Analysis - Dipak Mazumdar; Sanjib Banik; I. Das (New Trends in Physical Science Research Vol. 4, 2022)
In this chapter, we have discussed the ground state magnetism and nature of the critical exponents in the vicinity of phase transition temperature regions of (La1-xYx)0.7Ca0.3MnO3 (x = 0.3, 0.4, 0.5) compounds. All the compound undergoes continuous paramagnetic (PM) to ferromagnetic (FM) transition in addition to a spin-blocking transition. The doping of Y-ions on the La-sites strongly influences the magnetic properties of the compounds. Details isothermal magnetization measurements were carried out near the magnetic phase transition regions to study the critical fluctuations by using various traditional methods such as modified Arrott plot, Kouvel-Fisher method, critical isotherm analysis, and Widom scaling relation. The magnetic equation of state confirms the reliability and self-consistency of the calculated critical exponents. The obtained values of critical exponents are indicative of mean-field theory which suggests the existence of long-range ordered ferromagnetic exchange interaction in the studied (La1-xYx)0.7Ca0.3MnO3 (x= 0.3 and 0.4) compounds. However, with increasing the doping concentration (x = 0.5), the magnetic ground state is modified and can be explained from the framework of quenched disorder.